2017
DOI: 10.1063/1.4979310
|View full text |Cite
|
Sign up to set email alerts
|

Electric field measurement in the dielectric tube of helium atmospheric pressure plasma jet

Abstract: The results of the electric field measurements in the capillary of the helium plasma jet are presented in this article. Distributions of the electric field for the streamers are determined for different gas flow rates. It is found that electric field strength in front of the ionization wave decreases as it approaches to the exit of the tube. The values obtained under presented experimental conditions are in the range of 5–11 kV/cm. It was found that the increase in gas flow above 1500 SCCM could induce substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 49 publications
8
34
0
1
Order By: Relevance
“…If we instead assumed the streamer as a propagating conductor whose front had a finite curvature radius of ≈3 mm, E/N went up to ≈50 Td; hence, the BOLSIG+ simulation was performed in the E/N range between 5 and 50 Td. This range can indeed be reasonable, given that it has been experimentally confirmed, by means of the Stark polarization spectroscopy method, in a helium plasma source analogous to the PCC [31]. Figure 9 shows the ratio of the electron temperature to the ion mass T e /m i for pure helium and neon plasmas, as estimated by BOLSIG+.…”
Section: Plasma Fast Imagingsupporting
confidence: 52%
“…If we instead assumed the streamer as a propagating conductor whose front had a finite curvature radius of ≈3 mm, E/N went up to ≈50 Td; hence, the BOLSIG+ simulation was performed in the E/N range between 5 and 50 Td. This range can indeed be reasonable, given that it has been experimentally confirmed, by means of the Stark polarization spectroscopy method, in a helium plasma source analogous to the PCC [31]. Figure 9 shows the ratio of the electron temperature to the ion mass T e /m i for pure helium and neon plasmas, as estimated by BOLSIG+.…”
Section: Plasma Fast Imagingsupporting
confidence: 52%
“…Exactly like in the previously published studies on the same plasma system [24][25][26], the electric field values were measured using optical emission spectroscopy on a forbidden line of Helium (2 1 P-4 1 F), through the observation of its position in the spectrum with respect to the closest allowed line at 492.19 nm (2 1 P-4 1 D). The method is based on the work of Foster [27] and well described in more recent publications [28][29][30].…”
Section: Methodsmentioning
confidence: 99%
“…The gas flow speed was 1500 SCCM and all data shows properties of the freely expanding jet. larger in the pulsed jet (electron density for the AC jet has been estimated in [25] but not measured).…”
Section: Differences and Similarities Between Ac-and Pulse-driven Jetsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 12 ] These two reactions are the two main probable production reactions in the He/CO 2 plasma jet, [ 47 ] and require energetic electrons. Sretenović et al [ 48 ] showed that electron density in a streamer head in a capillary of a helium plasma jet, which is our case here, is related to the electric field strength in the streamer head. As the Townsend ionization coefficient depends on the local electric field, the evolution of the electron density can be estimated from this coefficient.…”
Section: Resultsmentioning
confidence: 61%